Neuroscience for early childhood education: impact on virtual settings and teaching practice - Ledesma-Pérez, Fernando; Cruz-Montero, Juana; Holguin-Alvarez, Jhon (Institute of Advanced Engineering and Science, 2024)
The research allowed us to measure the impact of neuroscience from the transfer carried out by practicing education teachers, who received university training based on neuroscience. We performed comparative inferential analyzes on 1,341 students from public and private schools in Lima who acted as an informant sample. The study sample was made up of 71 university students who worked as teachers with university training with neuroscientific content. Traceability was carried out between the macro and microprogramming of the university students and its effect on the school was calculated. Instruments were used to assess university content and measure school learning. It was found that 25% of the credits were transversal neuroscience subjects. In microplanning, more than 50% of the activities incorporated contributions from neuroscience, demonstrating significant effects on children’s learning. The limitations demonstrated the low scope focused on the number of teachers evaluated, the permeability of the neuroscientific concepts that could be delivered to school students due to the time delay involved in executing this type of activities. It is concluded that the activities were moderately significant in the development of the neuroscience curriculum for university students.